Molecular survey of Zika virus in the animal-human interface in traditional farming - Lopez-Apodaca, Laura Ivone; Zarza, Heliot; Zamudio-Moreno, Emily; Nuñez-Avellaneda, Daniel; Baak-Baak, Carlos Marcial; Reyes-Solis, Guadalupe del Carmen; Oswaldo Margarito, Torres-Chablé; Peláez-Ballestas, Ingris; Roiz, David; Suzán, Gerardo; Roche, Benjamin; Machain-Williams, Carlos Ignacio (Frontiers in Veterinary Science, 2022)
Backyard animal husbandry is common in rural communities in developing countries and, given the conditions in which it occurs, it can increase the risk of disease transmission, such as arboviruses. To determine the presence of the Zika virus (ZIKV) and abundance of its arthropod vectors we evaluated the socioeconomic implications involved in its transmission in two highly vulnerable Mayan communities in the state of Yucatan that practice backyard farming. An analytical cross-sectional study was carried out throughout 2016 to understand socioeconomic variables and seasonal patterns in mosquito populations. We selected twenty households from each community. Social exclusion indicators were analyzed, human and domestic animals were sampled, and mosquitoes were collected and identified. Four out of eight indicators of social exclusion were higher than the reported national averages. We captured 5,825 mosquitoes from 16 species being Culex quinquefasciatus and Aedes aegypti the most abundant. The presence of chickens and human overcrowding in dwellings were the most significant factors (P= 0.026) associated with the presence of Ae. aegypti. Septic tanks (odds ratio = 6.64) and chickens (odds ratio = 27.41) in backyards were the main risk factors associated with the presence of immature states of Ae. aegypti in both communities. Molecular analysis to detect ZIKV was performed in blood samples from 416 humans, 1,068 backyard animals and 381 mosquito pools. Eighteen humans and ten pig pools tested positive for ZIKV. Forty-three mosquito pools tested positive for flavivirus. Ten of the 43 pools of positive mosquitoes were sequenced, corresponding 3/10 to ZIKV and 1/10 to Dengue virus type 2. The findings obtained indicate the continuous circulation of Flavivirus (including ZIKV) in backyard environments in vulnerable communities, highlighting the importance of studying their transmission and maintenance in these systems, due that backyard animal husbandry is a common practice in these vulnerable communities with limited access to health services.